ANALISIS KEBUTUHAN PARKIR DI WILAYAH PASAR KARANG SUKUN: Analysis of Parking Demand in the Karang Sukun Market Area - Alexander Bali Ndara; Bagus Widhi Dharma S.; Aminullah Aminullah; Ni Made Nia Bunga Surya Dewi (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2026)
This study aims to determine the parking capacity and requirements for Karang Sukun Market in Mataram City, West Nusa Tenggara. It is a survey-based study employing a quantitative descriptive approach, conducted at the market from March 5 to March 12, 2025. The results indicate that parking volume and accumulation values ​​fluctuated across the observed time periods and days. However, peak values ​​generally occurred during the market's operational hours of 08:00–12:00 WITA, with a subsequent decline between 13:00 and 17:00 WITA. Parking capacity was sufficient on Tuesdays (both morning and afternoon) and Thursday afternoons (13:00–17:00), but proved inadequate on Mondays, Wednesdays, and Fridays. Fridays saw the highest visitor density, with a total of 668 vehicles parking. On average, the parking capacity at Karang Sukun Market was insufficient to meet demand; the facility accommodates 133 vehicles, whereas the average number of parked vehicles was 194. Due to this lack of adequate parking space, motorists resorted to parking along the streets surrounding the market, causing traffic congestion during peak hours.